25‐hydroxyvitamin D3 status is associated with developing adaptive and innate immune responses in the first 6 months of life. Issue 1 (January 2015) - Jones, A.P.; D'Vaz, N.; Meldrum, S.; Palmer, D.J.; Zhang, G.; Prescott, S.L.
Summary Background Vitamin D (25[OH]D3) status in early life has been linked to the risk of allergic disease in multiple observational studies. While immunomodulating properties are well recognized, there are few longitudinal studies of 25(OH)D3 status, immune function and allergic disease in infants. Objective To investigate 25(OH)D3 levels at birth [cord blood (CB)] and at 6 months of age in relation to immune function at 6 months of age, and clinical outcomes up to 30 months of age in infants with a maternal history of atopy. Methods In a subset of infants (n = 225) enrolled in a RCT (ACTRN12606000281594), 25(OH)D3 levels were assessed in relation to peripheral blood mononuclear cell cytokine responses to house dust mite (HDM), ovalbumin (OVA) and β‐lactoglobulin allergens, or Toll‐like receptor (TLR) ligands (lipopolysaccharide, lipoteichoic acid, polyinosinic : polycytidylic acid and CpG oligonucleotide) at 6 months of age, in addition to clinical outcomes (eczema, wheeze and allergen sensitisation) up to 30 months of age. Results Infants with higher 25(OH)D3 at birth (≥ 75 nmol/L, compared with < 50 nmol/L) had lower IL‐5 and IL‐13 responses to HDM by 6 months (P < 0.001 and P = 0.003, respectively). This was also reflected in strong inverse correlations between CB 25(OH)D3 levels and HDM IL‐13 (ρ = −0.57; P = 0.0002) and IL‐5 (ρ = −0.59, P = 0.0001) responses, with a similar trend for IL‐5 (ρ = −0.29; P = 0.009) responses to OVA. For innate stimulations, higher 25(OH)D3 levels at 6 months were associated with greater responses to TLR ligands. Additionally, higher CB 25(OH)D3 was associated with reduced risk eczema at 6 months (P = 0.011) and 12 months (P = 0.034). Conclusion This suggests that improving 25(OH)D3 status in pregnancy or early infancy may reduce the development of allergic disease in high‐risk infants by inhibiting cytokine profiles associated with allergy. Results of clinical trials are awaited to determine the efficacy of vitamin D supplementation in allergy prevention.